Development and external validation of a head and neck cancer risk prediction model - Smith, Craig D L; McMahon, Alex D; Lyall, Donald M; Goulart, Mariel; Inman, Gareth J; Ross, Al; Gormley, Mark; Dudding, Tom; Macfarlane, Gary J; Robinson, Max; Richiardi, Lorenzo; Serraino, Diego; et al. (Head & neck, 2024)
BACKGROUND: Head and neck cancer (HNC) incidence is on the rise, often diagnosed at late stage and associated with poor prognoses. Risk prediction tools have a potential role in prevention and early detection. METHODS: The IARC-ARCAGE European case-control study was used as the model development dataset. A clinical HNC risk prediction model using behavioral and demographic predictors was developed via multivariable logistic regression analyses. The model was then externally validated in the UK Biobank cohort. Model performance was tested using discrimination and calibration metrics. RESULTS: 1926 HNC cases and 2043 controls were used for the development of the model. The development dataset model including sociodemographic, smoking, and alcohol variables had moderate discrimination, with an area under curve (AUC) value of 0.75 (95% CI, 0.74-0.77); the calibration slope (0.75) and tests were suggestive of good calibration. 384 616 UK Biobank participants (with 1177 HNC cases) were available for external validation of the model. Upon external validation, the model had an AUC of 0.62 (95% CI, 0.61-0.64). CONCLUSION: We developed and externally validated a HNC risk prediction model using the ARCAGE and UK Biobank studies, respectively. This model had moderate performance in the development population and acceptable performance in the validation dataset. Demographics and risk behaviors are strong predictors of HNC, and this model may be a helpful tool in primary dental care settings to promote prevention and determine recall intervals for dental examination. Future addition of HPV serology or genetic factors could further enhance individual risk prediction.
Keywords: dospělí; logistické modely; United Kingdom; hodnocení rizik; Female; Europe; Adult; ženské pohlaví; Logistic Models; nádory hlavy a krku; lidé; Evropa; Spojené království; studie případů a kontrol; Risk Assessment; Risk Factors; Male; Head and Neck Neoplasms; Case-Control Studies; Aged; rizikové faktory; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans